Penggunaan Linear Programming Pada Optimalisasi Lahan Sempit di Masjid Baitul Izzah Islamic Center Tarakan Kalimantan Utara - Nurul Hidayat1; Chelsea Almaniah Setiawan; Azira Putri Andini; Nurzakina Nurzakina; Jiharka Jiharka; Satria Fauzhan Ramadhani; Mohammad Asri Dirvan (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study aims to optimize the use of limited land at the Baitul Izzah Islamic Center Mosque in Tarakan, North Kalimantan, by determining the combination of horticultural crops that yields the maximum profit. The method used is Linear Programming with the assistance of POM-QM software. The decision variables in this study consist of five types of crops, namely water spinach, eggplant, chili, Chinese cabbage, and scallions, which are grown in a raised bed system. The objective function of this study is to maximize profit based on the selling price and average yield of each crop. The optimization model is constrained by several factors, namely available land area, labor, and the availability of residual fertilizer. The mathematical model is formulated in the form of an objective function and constraint functions, then solved using the simplex method via the POM-QM software. The results of the study indicate that the optimal combination is achieved by planting 13.33 beds of chili peppers, yielding a maximum profit of Rp 22,156,670. These results indicate that chili plants provide the highest profit contribution compared to other crops under conditions of limited available resources. The application of Linear Programming to this limited land area can serve as a basis for decision-making in determining optimal and efficient cropping patterns for horticultural cultivation in the mosque environment.